2015
DOI: 10.4038/engineer.v48i1.6843
|View full text |Cite
|
Sign up to set email alerts
|

HEC-HMS model for runoff simulation in a tropical catchment with intra-basin diversions – case study of the Deduru Oya river basin, Sri Lanka

Abstract: Abstract:Hydrological modeling is a commonly used tool by water resource planners to simulate the hydrological response in a basin due to precipitation for the purpose of management of basin water. With the increasing demand for limited water resources in every basin, careful management of water resources becomes more important. The Deduru Oya river in Sri Lanka supplies water to number of new and ancient irrigation systems and the management of water resources in the Deduru Oya river basin, which has an area … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 5 publications
(1 reference statement)
0
17
0
Order By: Relevance
“…Part of the rainfall is lost through evapo-transpiration, interception of canopy and storage areas. Pervious areas are those into which rainfall infiltrates with no loss [32,33]. These are the areas that feed the baseflow.…”
Section: Rainfall Runoff Modelingmentioning
confidence: 99%
See 1 more Smart Citation
“…Part of the rainfall is lost through evapo-transpiration, interception of canopy and storage areas. Pervious areas are those into which rainfall infiltrates with no loss [32,33]. These are the areas that feed the baseflow.…”
Section: Rainfall Runoff Modelingmentioning
confidence: 99%
“…It has been widely applied worldwide with satisfactory results. HEC-HMS is a semi-distributed model that integrates land use and cover change [11,[30][31][32][33][34], like SWAT [8,12,[35][36][37][38][39]. However, comparative study based on model's hydrological processes, governing equations used, minimum data required and spatial as well as temporal scale of both HEC-HMS and SWAT concluded that HEC-HMS has the best efficiency and lightness [40,41].…”
Section: Introductionmentioning
confidence: 99%
“…Data collection is supposed to be one of the most challenging tasks in storm water management. 1 Khaniya et al 2 have obtained several data using field observations. Table 1 provides the data of the sub-basins including its catchment area, slope, impervious percentage, curve number (CN).…”
Section: Study Sitementioning
confidence: 99%
“…Mentioned that especially, developing countries around the world are facing these problems due to lack of understanding of the dynamics of the basin water and the assessment of basin water for development use. 1 Precipitation is identified as the major source of the fresh water; however, the water washes on the surface (semi impervious or impervious surfaces) is termed as runoff. Runoff water disturbs the basin hydrology which significantly reduces the groundwater recharge which can lower the groundwater table, increase run-off peak, runoff volume.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation